(untitled) (Sainmatika: Jurnal Ilmiah Matematika dan Ilmu Pengetahuan Alam, 2024)
The tropical climate gives rise to various kinds of tropical diseases, one of which can be caused by mosquitoes. The aim of this research was to determine the effectiveness concentration of lime leaf extract (Citrus aurantifolia) in repelling the Aedes aegypti mosquito. The research method used was an experiment by observing the effect of lime leaf extract as a natural mosquito repellent. Data processing used the one way anova statistical test, namely by using treatment plus 1 control in each treatment with 3 repetitions of the experiment. The results of this research were that there were differences in the treatment of orange leaf extract with a p-value (0.0005). The conclusion of the research is that the significant extract group is the 60 mg - 40 mg, 60 mg - 50 mg treatment, meaning that 60 mg of orange leaf extract treatment is the most effective as a natural insecticide.